Chapter Lost and found in translation Der alttschechische Barlaam zwischen kontemplativem Traktat, Predigt und Abenteuerroman - Rychterová, Pavlína (De Gruyter, 2015)
This book examines the ways that texts from the humanities have fostered particular approaches to knowledge by constructing different versions of a 'scientific ethos'. The studies contained in this volume reveal how and why different forms of scientific ethos have developed since the mid-18th century. The studies also illuminate associated styles of rhetorical argumentation.